The thought remolding campaign of the Chinese Communist Party-State - Hu, Ping, 1947- (ICAS publications series. Monographs, 2012)
This authoritative work on the Chinese Communist party's practices of reeducation and indoctrination, supersedes all previous works by bringing into account recent events. Hu Ping has provided a rich and rigorous study based not only in historical research and numerous compelling case studies of Chinese intellectuals, but also in a first person account of his own experience of Maoist thought "remolding." The Thought Remolding Campaign of the Chinese Communist Party-State is an important history not only of the reeducation programs, but of the interrogation processes of the Party, and the strategies of either evasion or reberllion that released prisoners adopted.